2018
DOI: 10.1016/j.neuroimage.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Decoding spoken phonemes from sensorimotor cortex with high-density ECoG grids

Abstract: For people who cannot communicate due to severe paralysis or involuntary movements, technology that decodes intended speech from the brain may offer an alternative means of communication. If decoding proves to be feasible, intracranial Brain-Computer Interface systems can be developed which are designed to translate decoded speech into computer generated speech or to instructions for controlling assistive devices. Recent advances suggest that such decoding may be feasible from sensorimotor cortex, but it is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
101
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 77 publications
11
101
0
1
Order By: Relevance
“…High gamma activity in ECoG in M1v concurred with Penfield's original somatotopic mappings of the articulators (Penfield and Boldrey, 1937). Several ECoG studies have found evidence that M1v activity roughly correlates with phoneme production (Bouchard et al, 2013;Lotte et al, 2015;Ramsey et al, 2017). Mugler et al demonstrated that single instances of phonemes can be identified during word production using ECoG from M1v and PMv (Mugler et al, 2014b).…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…High gamma activity in ECoG in M1v concurred with Penfield's original somatotopic mappings of the articulators (Penfield and Boldrey, 1937). Several ECoG studies have found evidence that M1v activity roughly correlates with phoneme production (Bouchard et al, 2013;Lotte et al, 2015;Ramsey et al, 2017). Mugler et al demonstrated that single instances of phonemes can be identified during word production using ECoG from M1v and PMv (Mugler et al, 2014b).…”
Section: Introductionmentioning
confidence: 66%
“…Over the last decade, electrocorticography (ECoG) has enabled identification of neural activity 48 with high spatial and temporal resolution during speech production (Blakely et al, 2008; Bouchard et 49 al., Several ECoG studies have found evidence that M1v activity roughly correlates with phoneme 53 production (Bouchard et al, 2013;Leuthardt et al, 2011;Lotte et al, 2015;Ramsey et al, 2017).…”
mentioning
confidence: 99%
“…Functional imaging (fMRI) studies generally provide corroborating evidence for the somatotopic cortical representation of the vocal tract effectors, among other body parts, albeit with a varying degree of overlap among individuals (Lotze et al, 2000;Hesselmann et al, 2004;Pulvermüller et al, 2006;Brown, Ngan, and Liotti, 2007;Meier et al, 2008;Takai, Brown, and Liotti, 2010;Carey et al, 2017). Recently, ECoG studies have elaborated the notion of cortical articulatory somatotopy by revealing differentiated neural representations for fine-grained phonetic features and complex kinematics underlying speech articulation (Bouchard et al, 2013;Bouchard & Chang, 2014;Mugler et al, 2014;Lotte et al, 2015;Bouchard et al, 2016;Cheung et al, 2016;Ramsey et al, 2017;Chartier et al, 2018;Conant et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…The spatio-temporal dynamics of word retrieval during speech production was shown in [6]. Other approaches demonstrated that speech can be decoded from invasively measured brain activity such as words [7], phonemes [8,9], phonetic features [10,11], articulatory gestures [12] and continuous sentences [13,14].…”
Section: Introductionmentioning
confidence: 99%